2013
DOI: 10.1002/jbm.b.32920
|View full text |Cite
|
Sign up to set email alerts
|

Biointeractivity-related versus chemi/physisorption-related apatite precursor-forming ability of current root end filling materials

Abstract: Commercial root end filling materials, namely two zinc oxide eugenol-based cements [intermediate restorative material (IRM), Superseal], a glass ionomer cement (Vitrebond) and three calcium-silicate mineral trioxide aggregate (MTA)-based cements (ProRoot MTA, MTA Angelus, and Tech Biosealer root end), were examined for their ability to: (a) release calcium (Ca(2+) ) and hydroxyl (OH(-) ) ions (biointeractivity) and (b) form apatite (Ap) and/or calcium phosphate (CaP) precursors. Materials were immersed in Hank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
124
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(132 citation statements)
references
References 51 publications
7
124
0
1
Order By: Relevance
“…Atmeh et al 18 demonstrated that Ca-Si cements facilitate the permeation of Ca and OH ions into the dentine, due to their caustic effect. It can be assumed that the improved ability to release remineralizing Ca and OH ions by Biodentine 19 is responsible for the improved formation of apatite at the interface 19,20 , and for micromechanical anchorage 21 . MTA HP showed improved push-out bond strength values compared with those of White MTA (p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Atmeh et al 18 demonstrated that Ca-Si cements facilitate the permeation of Ca and OH ions into the dentine, due to their caustic effect. It can be assumed that the improved ability to release remineralizing Ca and OH ions by Biodentine 19 is responsible for the improved formation of apatite at the interface 19,20 , and for micromechanical anchorage 21 . MTA HP showed improved push-out bond strength values compared with those of White MTA (p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…The hydroxyl ions released by the material are responsible for increasing the pH of the surrounding tissues. Biologically active materials, such as calcium silicate cements, can promote bone regeneration, and, for this reason, are recommended for healing periapical bone defects [41]. Furthermore, the release of hydroxyl ions during the hydration reaction creates an unfavorable environment for bacterial survival and proliferation [37].…”
Section: Discussionmentioning
confidence: 99%
“…Although it is possible that some of these represent calcium-deficient apatite with variable degrees of lattice substitutions by cations such as Na + and Mg 2+ and anions such as Cl − , it is likely some of these crystalline morphologies represent the intermediate octacalcium phosphate (OCP) phase described in classic calcium phosphate characterisation studies. Formation of an intermediate OCP phase by MTA or MTA-like materials was sparsely discussed in the endodontic literature except in a couple of studies [52,128]. Indiscriminate use of the term 'hydroxyapatite' (HA) in most of these endodontic studies is reflected by the inadequate chemo-analytical techniques employed for characterising the calcium phosphate precipitates.…”
Section: Mechanism Of Actionmentioning
confidence: 99%